Real-World Efficacy of Bevacizumab in Patients With Recurrent Epithelial Ovarian Cancer - Hung, Jo-Ni; Hsu, Shih-Tien; Sun, Lou; Hwang, Sheau-Feng; Liu, Chih-Ku; Shih, Yu-Hsiang; Chen, Ming-Jer; Wang, Jun-Sing; Lu, Chien-Hsing (Frontiers in Oncology, 2022)
Background: Bevacizumab in combination with chemotherapy prolonged the progression-free survival (PFS) of patients with recurrent epithelial ovarian cancer (EOC) in large-scale randomized controlled trials. However, real-world data for the use of bevacizumab in Asian patients with EOC is lacking. This study investigated the efficacy of adding bevacizumab to chemotherapy and compared it with that of chemotherapy alone in patients with recurrent EOC using real-world data from an Asian population. Method: We conducted a retrospective cohort study using data from a tertiary medical center in central Taiwan. Patients who had EOC with first relapse between 2011 and 2019 were enrolled. Patients’ medical histories, medication treatment, and relevant information were collected. The outcomes were PFS and overall survival (OS). The Kaplan-Meier plot was used to generate a survival curve for OS and PFS. Cox proportional hazard analysis was used to determine the associations of Bevacizumab treatment with OS and PFS with adjustment of relevant variables. Subgroup analyses were conducted to determine if there was a significant variation in the aforementioned associations. Results: After a median follow-up of 23 months, 67% of patients in the Bevacizumab group and 81% of patients in the non-Bevacizumab group had disease progression or death. There was no significant between-group difference in OS (p = 0.475). The median duration of PFS was 18.9 and 9.6 months, respectively, favoring those who were treated with Bevacizumab. After multivariate adjustment, treatment with Bevacizumab was associated with a lower risk of disease progression (hazard ratio 0.33, 95% CI 0.13-0.85, p=0.021). The improvement in PFS was consistent in the subgroups of different histological types, different disease stages at diagnosis, different treatment-free intervals, those undergoing or not undergoing secondary cytoreductive surgery, diverse chemotherapy regimens. Conclusion: Our findings provided crucial insights into the efficacy of bevacizumab for the treatment of recurrent EOC in the real-world setting.